化简cos²A+cos²(π/3-A)+cos²(π/3+A).
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 06:09:24
化简cos²A+cos²(π/3-A)+cos²(π/3+A).化简cos²A+cos²(π/3-A)+cos²(π/3+A).化简cos&
化简cos²A+cos²(π/3-A)+cos²(π/3+A).
化简cos²A+cos²(π/3-A)+cos²(π/3+A).
化简cos²A+cos²(π/3-A)+cos²(π/3+A).
cos2A+cos(π/3+A)+cos(π/3-A) =(cos2A+1)/2+{cos2(π/3+A)+1}/2+{cos2(π/3-A)+1}/2 =(cos2A+1)/2+{cos(2π/3+2A)+1}/2+{cos(2π/3-2A)+1}/2 ={3+cos2A+cos2π/3cos2A-sin2π/3sin2A+cos2π/3cos2A+sin2π/3sin2A}/2 =(3+cos2A-1/2cos2A-1/2cos2A)/2 =3/2,
化简cos²A+cos²(π/3-A)+cos²(π/3+A).
化简:cos²a+cos²b+sin²asin²b-cos²acos²b
化简sin²a+sinb²-sin²asin²b+cos²acos²b ,
化简sin²a+sinb²-sin²asin²b+cos²acos²b ,
化简 1. (1+tan²A)*cos²A 2. (1/cos²A)-tan²A 3.(1/cos²A)-tan²A-sin²化简 1. (1+tan²A)*cos²A 2. (1/cos²A)-tan²A 3.(1/cos²A)-tan²A-sin²详细点哦 谢谢~~~~
化简:(1+sin2a)/(cos²a-sin²a)
化简sin²a*tana+cos²acota+2sinacosa
化简 cos²(A+15)+cos²(A-15)-cos30cos2A
求证cos(a+b)*cos(a-b)=(cosa)^2-(cosb)^2从(cosacosb)²-(1-cos²a)(1-cos²b) 怎么得到cos²a-cos²b 不是cos²a+cos²b-1吗?
sin²a+cos²a/cos²a如何得到tan²a+1?
cos²(-a)-sin(-a)/ tan(2π+a)化简
化简sin²a+sinb²-sin²asin²b+cos²acos²b ,详细过程
求证:cos²a-sin²b=cos(a-b)cos(a+b)
化简:cos²1°+cos²;2°+……+cos²89°
化简cos²1°+cos²2°+cos²3°+…+cos²89°
请问为什么cos²Acos²B-sin²Asin²B=cos²A-sin²B
cosA/sinA=-12/5 sin²+cos²=1 求cos等于?所以25cos²A/144+cos²A=1
化简:(cos2a-cos²a)/(sin²a-1) =